ECONOMIC AND HUMAN RESOURCES IMPROVEMENT IN BOGOR CITY THROUGH ONLINE SALES STRATEGY, FINANCIAL REPORT MANAGEMENT, AND RESOURCE EMPOWERMENT AT KING JUICE FARHAN - Mekaniwati, Ani; Mulyana, Mumuh; Rosa, Wulan Wahuni; Ramadhan, Noval; Benekdita, Lucia (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2024)
Micro, small, and medium enterprises (MSMEs) are businesses classified based on factors such as number of employees, turnover, and total assets. These MSMEs contribute to local regional income, especially by creating jobs and income for the community. innovation and regional development. One of them is King Juice Farhan, which operates in the culinary sector, especially drinks and fruit salads. With an initial capital of 12 million rupiah from savings and support from his parents, King Juice Farhan provides 100 juice and fruit salad menus at affordable prices. Operating since 2021, this business has succeeded in opening two outlets in the Malabar and Ciheulet areas, with a total of 11 employees working in shifts at both outlets. The challenges faced by King Juice Farhan are From the results of interviews conducted with the owner of King Juice, Farhan, several pieces of information were obtained regarding partner problems, including: 1. Not maximizing the use of technology in aspects of online product marketing through paid advertising support, website design, and content planning on social media to increase sales, 2. Limited facilities in terms of production, especially related to equipment that is currently limited, 3. Lack of Owner Understanding in aspects of business management, especially in understanding the preparation of effective financial reports. The Kesatuan Business and Informatics Institute through Community Service activities strives to optimize King Juice Farhan's digital marketing and management, increase production and financial records so that King Juice Farhan can improve continuously.